2018
DOI: 10.1111/acer.13623
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxalase 1 (GLO1) Inhibition or Genetic Overexpression Does Not Alter Ethanol's Locomotor Effects: Implications for GLO1 as a Therapeutic Target in Alcohol Use Disorders

Abstract: The dose of pBBG used in this study is within the effective range shown previously to reduce EtOH drinking. Glo1 overexpression has been previously shown to increase EtOH drinking. However, neither manipulation altered the dose-response curve for EtOH's locomotor effects, whereas muscimol appeared to enhance the locomotor sedative effects of EtOH. The present data demonstrate that reduced EtOH drinking caused by GLO1 inhibition is not due to potentiation of EtOH's stimulant or depressant effects.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…In line with that, CamKIId expression shows also an increase in tumor cells and a downregulation in diabetic animal models. Therefore, we provide for the first time an explanation for phenomena that have been described for a long time in a broad range of experimental and clinical contexts (Santarius et al, 2010;Barkley-Levenson et al, 2018;Distler et al, 2012;Schalkwijk and Stehouwer, 2020;Kreycy et al, 2017;Wang et al, 2012;Rabbani and Thornalley, 2011). Further studies should focus on CamKIId expression and the effect toward activity of Glo1 in order to reveal new molecular linkages.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In line with that, CamKIId expression shows also an increase in tumor cells and a downregulation in diabetic animal models. Therefore, we provide for the first time an explanation for phenomena that have been described for a long time in a broad range of experimental and clinical contexts (Santarius et al, 2010;Barkley-Levenson et al, 2018;Distler et al, 2012;Schalkwijk and Stehouwer, 2020;Kreycy et al, 2017;Wang et al, 2012;Rabbani and Thornalley, 2011). Further studies should focus on CamKIId expression and the effect toward activity of Glo1 in order to reveal new molecular linkages.…”
Section: Discussionmentioning
confidence: 73%
“…However, alterations of Glo1 and its activity seem to play a pivotal role in various clinical contexts, such as diabetes (Rabbani and Thornalley, 2019), aging (Rabbani et al, 2016), as a potential drug target regarding cancer therapeutics (Antognelli et al, , 2019, but also as treatment against bacteria or protozoans (Thornalley, 1993;Santarius et al, 2010). Furthermore, psychological disorders, e.g., anxietylike behavior, as well as alcohol use disorders, have been linked to altered Glo1 (Barkley-Levenson et al, 2018;Distler et al, 2012). The aim of this study was to investigate the phosphorylation of Glo1, characterize responsible kinase(s), and describe consequences in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with previous studies that found that similar doses of pBBG had no effect on water, saccharin, or quinine drinking (McMurray et al, 2017b), did not exert a sedative effect as measured by the loss-of-righting reflex, and did not cause ataxia as measured in the balance beam task (McMurray et al, 2017b). Recent work has also shown that GLO1 manipulation does not alter the locomotor stimulant or depressant effects of alcohol, demonstrating that GLO1 inhibition does not reduce alcohol drinking simply by making alcohol more potent (Barkley-Levenson et al, 2017). However, the present study utilized a within-subjects design.…”
Section: Discussionmentioning
confidence: 99%
“…The OF test was administered to measure locomotor activity, as previously described. 22 , 23 , 24 , 25 Mice were moved into the testing room and allowed to acclimate for at least 30 min prior to testing. Testing took place between 10:00 and 12:00 h. Mice were placed in the center of a square chamber (43 × 43 × 33 cm; the size of the center was 26 × 16 cm), with dim overhead lighting inside of sound‐ and light‐attenuating boxes, and allowed to freely explore for 30 min.…”
Section: Methodsmentioning
confidence: 99%